(untitled) (Scientific journal of the Fergana State University, 2023)
The article based on the innovative approaches to teaching pedagogical skills in general secondary school student on the formation of technological compitencies, increases the effectiveness of compitencies of the lessons and helps them to become more professional in the future. The article describesthe mothod of organizing education using innovative programs in the teaching of technology. The student is able to fing a solutionto the problem situation, whichhelps the student have a high level of knowledge.